1989
DOI: 10.1055/s-2008-1046346
|View full text |Cite
|
Sign up to set email alerts
|

Canthaxanthin-Retinopathie ohne Canthaxanthin-Einnahme

Abstract: Seven patients are described who presented with the typical fundus finding of gold-colored crystals in the superficial layers of retina in the macular area (characteristic of canthaxanthin retinopathy) without having taken canthaxanthin-containing drugs. Canthaxanthin used as a food additive is discussed as a possible cause of the crystal deposition. There may be a rather high individual tendency to develop crystal deposition, possibly related to a metabolic defect affecting canthaxanthin kinetics or to pre-ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

1990
1990
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 1 publication
0
5
0
Order By: Relevance
“…In healthy patients, under normal physiological conditions, canthaxanthin does not appear in the macula lutea membranes. In most cases, its presence is connected with its consumption in high doses, and very rarely when no canthaxanthin has been ingested [2,[29][30][31][32][33]. Experiments on monkeys receiving an excess of canthaxanthin-containing fodder showed the level of canthaxanthin in the macula as high as 250 ng/g of wet tissue (approx.…”
Section: Macula Lutea Pigmentsmentioning
confidence: 99%
“…In healthy patients, under normal physiological conditions, canthaxanthin does not appear in the macula lutea membranes. In most cases, its presence is connected with its consumption in high doses, and very rarely when no canthaxanthin has been ingested [2,[29][30][31][32][33]. Experiments on monkeys receiving an excess of canthaxanthin-containing fodder showed the level of canthaxanthin in the macula as high as 250 ng/g of wet tissue (approx.…”
Section: Macula Lutea Pigmentsmentioning
confidence: 99%
“…Canthaxanthin is added to food, but it has been reported that the intake of foods with added canthaxanthin can lead to canthaxanthin retinopathy, retinal dystrophy and aplastic anemia (Oosterhuis, Remky, Nijinan, Craandijk & de Wolff, 1989;Sujak, 2009;McGuiness & Beaumont, 1985;Daicker, Schiedt, Adnet & Bermond, 1987;Hennekes, 1986;Bluhm, Branch, Johnston & Stein, 1990). Canthaxanthin is also used as a skin tanning agent in cosmetics (Lober, 1985;Baker & Gunther, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…It is interesting to note that the crystals diminish in numbers after the high-level intake of canthaxanthin has been stopped, although the law-level intake via food apparently continues as documented by the presence of a measurable base-line canthaxanthin plasma concentration. On the other hand, Oosterhuis et al (1989) have ascribed the ocurrence of retinal deposits in 7 patients, who claimed to not have taken canthaxanthin-containing tablets, to the intake of this carotenoid via food.…”
Section: Discussionmentioning
confidence: 99%